2022
DOI: 10.3390/environments9040049
|View full text |Cite
|
Sign up to set email alerts
|

Field Test of Mini Photoionization Detector-Based Sensors—Monitoring of Volatile Organic Pollutants in Ambient Air

Abstract: The determination of the concentrations of the organic compounds in ambient air using reference methods is a time-consuming process. The samples must be collected on a specific sorbent material and analyzed. In the best-case scenario, the analysis may be performed on site by portable chromatography techniques; otherwise, transport and laboratory analysis is necessary. Continuous sensory measurement is advantageous, especially concerning speed, resolution, price and ease of use. On the other hand, questions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For the calibration, all three varieties of PID sensors were exposed to compounds in a gaseous form prepared in the laboratory and analyzed by gas chromatography; a detailed description is given in our previous work [13]. We also concluded that in mixtures of compounds, the responses of the sensors are additive but highly inconclusive and incalculable; the best way to estimate the concentration was a simple linear regression of signals derived from benzene concentrations.…”
Section: Pid Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the calibration, all three varieties of PID sensors were exposed to compounds in a gaseous form prepared in the laboratory and analyzed by gas chromatography; a detailed description is given in our previous work [13]. We also concluded that in mixtures of compounds, the responses of the sensors are additive but highly inconclusive and incalculable; the best way to estimate the concentration was a simple linear regression of signals derived from benzene concentrations.…”
Section: Pid Sensorsmentioning
confidence: 99%
“…Field tests focused on sensor response and cross-sensitivity have been conducted with respect to intended use [7][8][9], but recently, questions arose as to whether such field-calibrated sensors can be relocated [10,11]. Taking into account the behavior of the used sensors from long-term AQM [12,13], we checked the sensors for changes in behavior, and differences in measured concentrations of larger than 20% detected during routine checking compared to the previous measurement periods were considered as a sign of excessive wear and end of service lifetime; thus, such sensors discarded and replaced with new ones.…”
Section: Sensor Theory and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has significant effects on important functional indicators of the PID, including the detection limits and accuracy of VOC monitoring. Furthermore, the ultraviolet lamp directly influences key performance indicators of the PID, such as power consumption, lifespan, and size [24,25]. To ensure proper transmission, the ultraviolet lamp requires a material with specific lattice constants as the window material to facilitate the transmission of vacuum ultraviolet photons necessary for photoionization detection.…”
Section: Pid Selection In the Workmentioning
confidence: 99%
“…Finally, the median average filtering method is applied for the optimal sensor data, and the data of the VOC monitoring sensor with a high signal-to-noise ratio can be obtained. At present, the noise of the PID signal is mostly filtered by median filtering and the low-pass filtering method [13]. The two filtering means separate the useful signal and the noise signal in the time domain by Fourier transform in the frequency domain, but the separation can be completed only when the useful signal and the noise signal are not mixed together, and the noise of the signal is often distributed in the whole frequency domain, so when removing the noise, the useful signal is often removed.…”
Section: Introductionmentioning
confidence: 99%